MRI monitoring of the effect of tissue interfaces in the penetration of high intensity focused ultrasound in kidney in vivo - Damianou, Christakis A. (My University, 2004)
In this paper, we studied the effect of interfaces during the application of high intensity focused ultrasound (HIFU) ablation in rabbit kidney in vivo. In kidney ablation, mainly two types of interfaces are encountered: these are muscle-kidney and fat-kidney. It was observed that the intensity for which the probability of cavitation (POC) is one was decreased when HIFU penetrated through interfaces, meaning that an interface is a potential site of cavitation. We utilized the concept of scanning the area to be treated in two dimensions (rectangular grid) by applying low intensity ultrasound (diagnostic scan). When all the points of the grid show decrease of signal in T1-weighted fast spoiled gradient (FSPGR) which indicated heating, complete necrosis was observed in the targeted area during the application of HIFU (therapeutic scan). If ultrasound goes through an interface that includes air spaces, the diagnostic scan indicates spaces with poor ultrasound penetration and as a result, during the application of the therapeutic scan, some sites remain untreated. The muscle-kidney and fat-kidney interfaces cause reflection of ultrasound, which prevents the penetration of ultrasound. Microscopic bubbles in the interface may initiate cavitation, especially at high intensities. However, sometimes these types of interfaces do not include any bubbles and therefore the propagation of ultrasound is not inhibited. © 2004 World Federation for Ultrasound in Medicine & Biology.
Keywords: Cavitation; Interface; Kidney; MRI; Ultrasound